Pengaruh Komunikasi Organisasi, Komitmen Organisasi, dan Lingkunan Kerja terhadap Kepuasan Masyarakat melalui Kualitas Pelayanan sebagai Variabel Intervening (Studi Kasus di Dinas Dukcapil Brebes) - Agustian Maulana; Slamet Bambang Riono; Ari Kristiana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the influence of organizational communication, organizational commitment, and work environment on community satisfaction through service quality as an intervening variable. This research was conducted at the Population and Civil Registration Service (Dinas Dukcapil) of Brebes Regency using quantitative research methods. The research subjects were all employees of the Brebes Dukcapil Service, while the research object was the influence of the independent variables (organizational communication, organizational commitment and work environment) on the dependent variable (community satisfaction) through the intervening variable (service quality). The research population is all the people of Brebes Regency who have come to the Brebes Dukcapil Service, especially in the period October-December 2023, totaling 1,100 people. The sampling technique used was simple random sampling with a sample of 92 people. Research data was collected through questionnaires distributed to respondents and analyzed using Structural Equation Modeling (SEM) analysis techniques. The research results show that: Organizational communication has a positive and significant effect on service quality. Organizational commitment does not have a significant effect on service quality. The work environment has a positive and significant effect on service quality. Organizational communication does not have a significant effect on community satisfaction. Organizational commitment does not have a significant effect on community satisfaction. The work environment has a positive and significant effect on people's satisfaction. Service quality has a positive and significant effect on community satisfaction. Service quality mediates the influence of organizational communication on community satisfaction. Service quality does not mediate the relationship between organizational commitment and community satisfaction. Service quality mediates the influence of the work environment on people's satisfaction.